Directives Used in Class Interactions by Grade 4A and 4B During Teaching and Learning Process at Primary School of Green School - Susanti, I Luh Meiyana Ariss (Universitas Pendidikan Ganesha, 2019)
This study was aimed at analyzing the types and the functions of directives used by teachers and pupils in class interactions during teaching and learning process. The subjects of this study were the teachers and the pupils in grade 4A and 4B of Green School. The data were collected in the form of verbal interactions. There were two instruments used in conducting this study, namely observation sheet and recording camera. The result of analysis showed both teachers and pupils tend to use bald imperatives in class interactions during teaching and learning process and they mostly used directives to request someone to do certain action. The number of bald imperatives which were used by teachers were 116 utterances meanwhile the pupils used 38 utterances. The teachers used directives to request someone to do certain action in 146 utterances meanwhile pupils used directives 56 utterances to request someone to do certain action.